EVALUASI PROGRAM PEMBINAAN TIM BOLA VOLI OLEH KOMITE OLAHRAGA NASIONAL INDONESIA KABUPATEN CIAMIS - Fahrul Roji; Aan Anwar Sihabudin; Ii Sujai (JOURNAL SAINS STUDENT RESEARCH, 2025)
The Indonesian National Sports Committee (KONI) is an authorized institution responsible for the development and advancement of sports achievements in Indonesia. At the regional level, KONI collaborates with the local government in providing facilities, organizing activities, and budgeting funds. One implementation of this role is the development of volleyball teams in Ciamis Regency. Volleyball is a highly popular sport that offers physical, social, and economic benefits to the community. However, the performance of the Ciamis volleyball team in the PORPROV (Provincial Sports Week) event has shown inconsistent results, particularly in the women’s division. This study aims to evaluate the volleyball team development program conducted by KONI Ciamis using a descriptive qualitative approach and the CIPP evaluation model (Context, Input, Process, Product). Data were collected through interviews, observations, and documentation, involving eight informants: the Chair of KONI, Chair of PBVSI, two club owners, two coaches, and two volleyball athletes. Data analysis techniques include: data collection, data reduction, data display, and conclusion drawing with verification. The results show that in the context dimension, the program was formulated collaboratively with clear goals. However, the input dimension still faces challenges in the quality of coaches and limited facilities and infrastructure. The process dimension faces technical challenges such as budget delays. In the product dimension, there are long-term positive impacts, yet the achievements in the women’s division remain suboptimal. Overall, the development program is running fairly well but requires improvements in human resources, facilities, and planning for more equitable and sustainable success.